FAP-CAR-T cells reduce dystrophic muscle fibrosis, improving adeno-associated virus gene transfer efficacy - Maxime Ferrand; Céline J. Rocca; Guillaume Corre; Valentina Buffa; Sophie Frin; Francine Garnache-Ottou; Elodie Bôle-Richard; Sonia Albini; Isabelle Richard; Anne Galy (Molecular Therapy: Methods & Clinical Development)
Tissue fibrosis is a pathological feature of many diseases including muscular dystrophies such as Duchenne muscular dystrophy (DMD). Fibrosis may limit the effectiveness of gene therapy in muscle impacting on viral dosing but direct evidence is lacking. Strategies to reduce skeletal muscle fibrosis are limited. The fibrosis Fap gene is over-expressed in the skeletal muscles of a severe mouse model of DMD, suggesting that cells expressing membrane fibroblast activation protein (FAP) could be targeted by chimeric antigen receptor (CAR)-T cells. Two consecutive administrations of FAP-specific CAR-T cells in the severe DMD model reduced collagen deposits and fibrotic biomarkers and also reduced the number of FAP-positive cells in muscle. Single cell transcriptomics revealed that FAP-CAR-T cells triggered cellular interactions with otherwise inactive muscle resident macrophages and depleted specific subsets of FAP-highly-expressing fibro-adipogenic progenitor cells, pointing to their importance in the fibrosis process. Reducing fibrosis with FAP-CAR-T cells enhanced adeno-associated virus (AAV) microdystrophin gene transfer in the model by increasing vector copies, demonstrating that fibrosis is a restriction factor for AAV gene delivery in skeletal muscle. These results provide novel insights into therapeutic strategies for DMD or other fibrotic diseases.